On anisotropy evolution in finite strain plasticity. Issue 1 (17th December 2018) - Kaiser, Tobias; Lu, Jia; Menzel, Andreas; Papadopoulos, Panayiotis
Abstract: Motivated by the experimental investigations on cold rolled sheet metal presented in [1], this contribution focuses on a specific modelling approach to capture the evolution of (plastic) material symmetry groups that is induced by finite plastic deformation processes. The ensuing developments are based on the general theoretical framework by Lu and Papadopoulos with regard to evolving material symmetries proposed in [2, 3]. In particular, we elaborate a specific form of the evolution equation for the structural tensor that characterises the respective material symmetry group and show that the simulation results are in good accordance with the experimental findings.